Development of a Genomic Resource and Identification of Nucleotide Diversity of Yellow Perch by RAD Sequencing - Guo, Liang; Yao, Hong; Shepherd, Brian; Sepulveda-Villet, Osvaldo J.; Zhang, Dian-Chang; Wang, Han-Ping (Frontiers in Genetics, 2019)
Yellow perch (Perca favescens) is an important native North American fish in ecology and aquaculture. However, molecular markers are minimal for this species, especially those with genome-wide distribution. Single sequence repeat markers are always developed based on sequences from a single individual, which is time consuming with a low success rate. In this study, combining data from HiSeq and MiSeq platforms, we applied restriction site-associated DNA sequencing (RAD-Seq) to yellow perch geographic demes to develop large numbers of polymorphic genetic markers, including single nucleotide polymorphisms and simple sequence repeats, and to evaluate nucleotide diversity. A total of 258,056 contigs were assembled with the length of 605 ± 71 (mean ± SD) bp, which were longer than those just using HiSeq data. Nucleotide diversity (π) was 0.00304 with 95% confidence intervals from 0.00303 to 0.00304. Based on the assembled sequences, a total of 59,766 perfect single sequence repeats were detected, with AC/GT being the most common repeat motif and GC being the rarest. Based on this breeding population, 41,736 high-quality single nucleotide polymorphisms and 10,412 polymorphic single sequence repeats were obtained. Validation of amplification by randomly selecting 40 polymorphic single sequence repeats showed a high success rate (85%). Our approach for polymorphic single sequence repeats development enables new usage of data from RAD-seq techniques. These developed markers could be used in finfish broodstock management, genetic improvement and resource conservation, and would contribute to sustainable development of fisheries and the aquaculture industries.